EFFECT OF AMELIORATION AND K FERTILIZATION ON POTASSIUM Q-I RELATIONSHIP PARAMETERS ON ACID MINERAL SOIL - SUBIKSA, I GUSTI MADE; ADININGSIH, J SRI; SUDARSONO, .; SUBIHAM, SUPANDI (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2004)
Relationship between cations adsorbed in solid phase (Qfactor) and those in soil solution (I-factor) can be expressed by quantity-intensity (Q-I) relationship curve of K that was introduced by Beckett. A laboratory experiment to study the effect of amelioration and K fertilization on K Q-I parameters was carried out on three soil families of acid upland mineral soil from Cigudeg, Kentrong, and Papanrejo. The experiment was arranged using completely randomized design with 2 factors. The first factor was three kinds of ameliorant and the second factor was three levels of K fertilization. The result suggested that amelioration with dolomite and steel slag increased K buffering capacity (PBCK) due to the increase in cation exchange capacity (CEC) and Ca and Mg concentration of the soil solution.Conversely, amelioration decreased equilibrium activity ratio of K (ARKe) due to alteration of K-Ca?Mg equilibrium. Amelioration, however, did not affect labile-K, except for Cigudeg soil. The application of K fertilizer increased K availability in terms of ARKe and labile-K. Those three soil families performed different changes in K availability effect, where soil with higher CEC showed smaller change than the lower one, also tended todecrease K buffering capasity (PBCK). The implication of this study is amelioration practice must be followed by K fertilization in order to avoid plant deficiency in K nutrient.